PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKn) DENGAN MENGGUNAKAN PENDEKATAN KONSTRUKTIVIS DI SEKOLAH DASAR - SIRMALINI, SIRMALINI (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Source of data is process is process study of PKn with this research subjek is class student of IV amounting to 24 people. Researcher act as practitioner. Result of obtained research of perception of RPP cycle of I 73,21% and cycle of II 96,43%. ( 2) Execution of study done/conducted as according to Plan Execution of Study which have been compiled, obtained value of aspect assessment of teacher is  at cycle of I 77,08 % and [at] cycle of II 97,92 %, while at aspect assessment of cycle student of I 75,00% and cycle of II 97,92 %. ( 3) expected Assessment by using Approach of konstruktivisme have mounted. Mean result of learning student at cycle of I is 80,59 % and 90,05 % at cycle of II. got Conclusion of this research that applying of approach of study of konstruktivis can improve result learn PKn student in class of IV SDN 09 Mount of Tuleh Sub-Province of Pasaman West.   Kata kunci : hasil ; belajar; pendekatan ; konstruktivis